2019
DOI: 10.1007/978-3-030-21642-9_6
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Fall Detection System Using Recurrent Neural Networks

Abstract: Falls are the most common cause of fatal injuries in elderly people, causing even death if there is no immediate assistance. Fall detection systems can be used to alert and request help when this type of accident happens. Certain types of these systems include wearable devices that analyze bio-medical signals from the person carrying it in real time. In this way, Deep Learning algorithms could automate and improve the detection of unintentional falls by analyzing these signals. These algorithms have proven to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Vision based systems work with the data from RGB and Depth camera of Kinect shown in [63], [64], [80], [81], [98], [100], [107], [108], RGB Cameras introduced in [67], [69], [76], [78], [82], [85], [96], [97], [108]. Sensor based systems work with accelerometer data shown in [70], [72], [74], [77], [79], [99], [102]- [106], gyroscope data depicted in [70], [104], radar data demonstrated in [69], [71], [116], [119]. Comparing both categories, vision based systems provide better result than sensor based system.…”
Section: A Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vision based systems work with the data from RGB and Depth camera of Kinect shown in [63], [64], [80], [81], [98], [100], [107], [108], RGB Cameras introduced in [67], [69], [76], [78], [82], [85], [96], [97], [108]. Sensor based systems work with accelerometer data shown in [70], [72], [74], [77], [79], [99], [102]- [106], gyroscope data depicted in [70], [104], radar data demonstrated in [69], [71], [116], [119]. Comparing both categories, vision based systems provide better result than sensor based system.…”
Section: A Discussionmentioning
confidence: 99%
“…Real-time monitoring is another important factor in fall detection systems, as fall events occur in a very short period of time and quick response after fall events are paramount to patient survivability. Out of the reviewed systems, the systems proposed in [64], [67], [70], [72], [80], [81], [82], [85], [98], [100], [102], [104], and [105] have reported realtime performance.…”
Section: A Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results obtained in [33] showed that the regularization of sample values substantially improves the effectiveness. To achieve this, a batch normalization layer is included at the beginning of the architecture.…”
Section: Methodsmentioning
confidence: 99%